Morphological and post-harvest characteristics of promising potato clones under conditions of the state of Trujillo Venezuela (Agroindustria, Sociedad y Ambiente, 2024)
The potato is the fourth most important food crop in the world. Potato yields are linked to improved seed, varieties, tillage, irrigation, fertilization, and pest and disease control. This work was carried out with the purpose of evaluating important agronomic characteristics of 5 advanced clones and a variety of potatoes, in the La Cristalina Sector of the state of Trujillo-Venezuela, an important area in the production of this sector. The study was carried out at the La Cristalina Experimental Field, at 2,630 meters above sea level. A completely randomized block experimental design was used with four repetitions for each treatment. Five clones from CIP were evaluated: 393371-159; 393280-64; 392639-34; 391011-17 and 393371-58 and the Mukasinia variety. The evaluation of the response variables was growth, flowering, yield and postharvest. The Mukasinia variety presented better behavior in terms of emergence. Clones 393371-159; 392639-34 and 393280-64 had similar numbers of stems per plant. All clones and the variety showed an erect habit, in addition to leaf sizes between small and medium. The beginning of flowering occurred between 69 and 74 days after sowing. The flower color for the Mukasinia variety and clones 392639-34 and 391011-17 was white. The highest average yield was obtained in clone 393371-159. The lowest yield was presented by the Mukasinia variety. Finally, clones 391011-17; 393280-64; 393371-58 and the Mukasinia variety had smooth skin and superficial eyes and cream flesh color.
Keywords: Solanum tuberosum, clones, growth.